Computational investigation and screening of [1, 2, 4]triazolo[4, 3‐b][1, 2, 4, 5]tetrazine‐based high energy materials. (2nd November 2020) - Liu, Luhao; Jin, Xinghui; Zhou, Jianhua; Hu, Bingcheng
Summary: In the present work, some [1, 2, 4]triazolo[4, 3‐b][1, 2, 4, 5]tetrazine‐based high energy compounds were designed. The electronic structures, heats of formation (HOF), detonation velocities ( D ), detonation pressures ( P ), and thermal stabilities (BDEs) of the titled high energy materials were calculated at B3LYP/6‐311G (d, p) theoretical level of DFT method. Based on the calculated data, the frontier molecular orbital energy gaps were from 1.02 (B2) to 3.91 eV (A4), the values of HOF, D, P, and BDEs were from 1020.6 (A4) to 2286.3 kJ mol −1 (D2), from 6.52 (A1) to 9.44 km s −1 (D8), from 17.5 (A1) to 41.5 GPa (D8), and from 36.1 (D2) to 515.5 kJ mol −1 (B1), respectively. Take D, P, and BDEs into consideration, seven compounds (A8, B8, C8, D7, D8, E8, and F8) were screened as potential candidates for high energy materials due to their high detonation properties ( D and P ) and proper thermal stabilities. Finally, the electronic structures (such as distribution of frontier molecular orbitals and electrostatic potentials) were presented, which may provide a new research direction to high energy materials. Abstract : A series of [1, 2, 4]triazolo[4, 3‐b][1, 2, 4, 5]tetrazine‐based high energy density materials were designed and their properties were investigated fully based on B3LYP/6‐311G(dp) method of density functional theory.